Xenomania on Cafe Menu Lists in Solo and Its Implementation in The Learning of Indonesian Text Procedure in Middle Schools - Sundava, Soleh; Sulistyono, Yunus (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
The phenomenon of linguistic xenomania is currently unknowingly developing widely and has been used in the social realm of coffee shops or cafes. Of the several cafes in Solo that use foreign languages, they include the Coffee Bagaia Bersama cafe and Eden Soc which are located in the city of Solo. This research aims to 1) find out the form of use of foreign languages in the menu list in a coffee shop in Solo, 2) find out why the managers of Bahagia Bersama and Eden Soc cafes use foreign languages in the menu list, and 3) find out the implementation of xenomania in the cafe menu list in Solo. Solo in learning procedure texts in junior high school. The data collection techniques that researchers use are interviews, documentation and observation. The subjects in this research are the managers of the Coffee Bahagia Bersama cafe and Eden Soc cafe, while the object of this research is the menu of the Coffee Bahagia Bersama cafe and Eden Soc cafe. This research has concluded the results of research from two coffee shops in Solo. The research findings consist of 1) the use of foreign languages in the Bahagia Bersama and Eden Soc cafe menu lists, French fries, one example of a form of xenomania which means French fries which are named after the use of foreign language to become French fries. 2). The reason why the managers of the Bahagia Bersama and Eden Soc coffee cafes prefer to use foreign languages in the menu list, the managers of the two coffee shops use foreign languages in their menu lists because it is to attract the attention of buyers or readers. The managers even explained that using a foreign language can provide a strong attraction. strong towards buyers. 3). Implementation of xenomania on cafe menu lists using procedure text learning. The implementation of xenomania on the cafe menu is one of the procedural texts, the steps for making lychee tea in junior high school. In implementation, researchers used guidelines for the syllabus of the 2013 curriculum (K-13). The researcher made a comparison between middle school procedure text learning and high school procedure text learning.